Supercritical Heat Transfer and Pyrolysis Characteristics of n-Decane in Circular and Rectangular Channels - Zhiliang Lei; Zewei Bao (Energies, 2023)
In this research, the effects of different channel cross-section shapes on the flow, heat transfer and pyrolysis characteristics of n-decane were analyzed and compared based on CFD simulations. The interactions between cracking, heat transfer and flow field in a circular tube and a rectangular tube were studied. The results showed that the mean pressure drop in the rectangular channel is 1.18 times as high as that in the circular channel with pyrolysis due to its smaller equivalent diameter. The maximum value of the chemical heat sink in the rectangular channel is 1.6 times as high as that in the circular channel. The high temperature zone of any cross section in the rectangular channel is much larger than that in the circular channel due to the superposition of the boundary layer and lower turbulent kinetic energy in the corners of the rectangular channel. The maximum value of the Nu in the circular channel is 1.3 times as high as that in the rectangular channel with pyrolysis due to larger heat capacity, lower viscosity and higher wall shear stress.